Control of Smooth Muscle Cell Proliferation – The Role of the Basement Membrane - Hedin, Ulf; Roy, Joy; Tran, Phan Kiet; Lundmark, Karin; Rahman, Adnan (Thrombosis and Haemostasis, 1999)
In atherogenesis and in response to vessel injury, arterial smooth muscle cells (SMCs) are activated from a quiescent, differentiated state into an actively proliferating and synthetic phenotype which migrate into the intima where the cells participate in the formation of a fibrous plaque or intimal hyperplasia. The mechanisms involved in the control of SMC function are not clear and no preventive therapy against SMC activation is available. Interactions between SMCs and the extracellular matrix have been shown to influence SMC structure and function through integrin-mediated signaling processes. The SMC basement membrane is a specific form of extracellular matrix which seems to be crucial for the maintenance of SMC quiesence and the disruption of these interactions is part of cellular activation after atherogenic or traumatic stimuli. This concept of “negative growth control” may constitute a future target for the development of new strategies in the prevention of SMC activation in atherogenesis and restenosis formation.
Keywords: Smooth muscle cells; restenosis; atherogenesis; cellular activation; basement membrane; integrins